Combined Effects of Bacteriocin-Like Inhibitory Substances from Vaginal Lactobacillus Isolated from Clinical Sample on Group B Streptococcus - Brown, Samuel Tamunoiyowuna Cockeye; Mohammed, Usman Ikrimah; Onyemaechi, Eze Emmanuel; Daniel, Benjamin Nanisi (Darul Yasin Al Sys, 2025)
This study investigates the prevalence of Group B Streptococcus (GBS) and the potential inhibitory effects of bacteriocin-like substances produced by Lactobacillus species in pregnant women in Wukari, Taraba State, Nigeria. Lactobacillus species, known as non-pathogenic Gram-positive rods, are commonly found in the vaginal microbiota of healthy premenopausal women, where they play a crucial role in maintaining vaginal health through their antimicrobial properties. The study aimed to determine the incidence of GBS colonization and explore the antimicrobial activity of crude and partially purified bacteriocin-like inhibitory substances from Lactobacillus isolates against both Gram-positive and Gram-negative bacteria. A total of 50 vaginal swab samples were collected from pregnant women. The results revealed that 11 women (22%) were colonized by Group B Streptococcus, while 14 women (28%) tested positive for Lactobacillus presence. The bacteriocin-like inhibitory substances produced by the Lactobacillus isolates demonstrated significant antimicrobial activity against GBS, with optimal inhibitory effects observed at 30°C and pH 5.5. Furthermore, antibiotic susceptibility testing showed that ciprofloxacin, erythromycin, chloramphenicol, and streptomycin were effective against GBS isolates. The findings underscore the potential role of Lactobacillus-derived bacteriocins as natural antimicrobial agents in the prevention and control of GBS infections, particularly in pregnant women. This study also reinforces the importance of monitoring GBS colonization due to its implications for maternal and neonatal health.